2017
DOI: 10.1002/col.22184
|View full text |Cite
|
Sign up to set email alerts
|

Does uniform color affect offside in association football?

Abstract: Past research has documented an impact of sportswear color on performance and referees' judgments in combat and team sports. Amongst other things, it was argued that these effects may arise from differences in visibility. In this regard, the current study was aimed at questioning the impact of uniform color on offside judgments in association football. We analyzed the number of offside judgments for 1530 matches from the first and second division of the football league in Germany and recorded the color of shir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
(164 reference statements)
0
2
0
1
Order By: Relevance
“…A relatively recent yet growing body of literature is focusing on the psychological, physiological, and behavioral effects of perceiving colors and colored environments. The visual properties of colors seem to hold specific meanings that are centrally processed and thought to influence affects, perceptions, cognitions, as well as intellectual and motor performances (e.g., Elliot et al, 2007; Briki et al, 2015; Briki and Hue, 2016; Krenn, 2018; Lee et al, 2018; Zhang et al, 2018). Early studies on color psychology started on animal species and emphasized the association between physical red coloration and male dominance (e.g., Milinski and Bakker, 1990; Pryke et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A relatively recent yet growing body of literature is focusing on the psychological, physiological, and behavioral effects of perceiving colors and colored environments. The visual properties of colors seem to hold specific meanings that are centrally processed and thought to influence affects, perceptions, cognitions, as well as intellectual and motor performances (e.g., Elliot et al, 2007; Briki et al, 2015; Briki and Hue, 2016; Krenn, 2018; Lee et al, 2018; Zhang et al, 2018). Early studies on color psychology started on animal species and emphasized the association between physical red coloration and male dominance (e.g., Milinski and Bakker, 1990; Pryke et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The literature contains only a single study that has addressed the impact of shirt colors on offside judgments in soccer. In this study, Krenn ( 2018 ) used videos of 1,530 matches from the first two divisions of the German Soccer Association to investigate the relationship between the dress colors of the defending and the attacking team, respectively, and the number of offside decisions. Krenn found that the frequency of offside decisions against the attacking team was reduced when the forwards wore black shirts.…”
Section: Discussionmentioning
confidence: 99%
“…Aufgrund dieser diversen Einflussmöglichkeiten wurde in den Achtzigern von der NASA (National Aeronautics and Space Administration) eine Meta-Studie in Auftrag gegeben, um die farbpsychologischen Befunde aus über 200 Studien zu aggregieren und so die "hability in the design of space stations interiors" zu verbessern (Beach et al 1988). Mahnke et al (2007) Frank und Gilovich 1988;García-Rubio et al 2011;Greenlees et al 2008;Hagemann et al 2008;Hill und Barton 2005;Krenn 2018;Olde Rikkert et al 2015;Piatti et al 2012;Rowe et al 2005;Weinberg et al 1980).…”
Section: Einfluss Von Farben Bei Veranstaltungenunclassified